Inhibition of cathepsin X enzyme influences the immune response of THP-1 cells and dendritic cells infected with Helicobacter pylori - Skvarč, Miha (Radiology and oncology (Ljubljana), 2013)
Background. The immune response to Helicobacter pylori importantly determines the outcome of infection as well as the success of eradication therapy. We demonstrate the role of a cysteine protease cathepsin X in the immune response to H. pylori infection. Materials and methods. We analysed how the inhibition of cathepsin X influenced the immune response in experiments when THP-1 cells or dendritic cells isolated from patients were stimulated with 48 strains of H. pylori isolated from gastric biopsy samples of patients which had problems with the eradication of bacteria. Results. The experiments, performed with the help of a flow cytometer, showed that the expression of Toll-like receptors (TLRs), especially TLR-4 molecules, on the membranes of THP-1 cells or dendritic cells was higher when we stimulated cells with H. pylori together with inhibitor of cathepsin X 2F12 compared to THP-1 cells or dendritic cells stimulated with H. pylori only, and also in comparison with negative control samples. We also demonstrated that when we inhibited the action of cathepsin X in THP-1 cells, the concentrations of pro-inflammatory cytokines were lower than when THP-1 cell were stimulated with H. pylori only. Conclusions. We demonstrated that inhibition of cathepsin X influences the internalization of TLR-2 and TLR-4. TLR-2 and TLR-4 redistribution to intra-cytoplasmic compartments is hampered if cathepsin X is blocked. The beginning of a successful immune response against H. pylori in the case of cathepsin X inhibition is delayed.
Keywords: cathepsin X; dendritic cells; dendritične celice; katepsin X; macrophage; makrofagi